Study on Locating Techniques of Single-phase Grounding Fault in Distribution Network - Wang Jianmin; Shen Weiwei; Chen Yanping; Jin Xin; Shi Jidong; Wang Dongju (Institute of Advanced Engineering and Science, 2014)
The single-phase grounding fault has great negative influence on neural ineffectively grounding system of distribution network. This article has illustrated and compared commonly used fault locating techniques including the impedance method, travelling wave method and signal injection method. The author has detailed how fault locating could be realized and merits and shortcoming of each method. It is shown that every method still has its own space of improvisation. And the rapid development of smart grid has given directions to further researches. On one hand the current problems of fault location have been revealed in this essay. One step further, this article has made expectations for achieving more accurate and timely fault locating methods. DOI : http://dx.doi.org/10.11591/telkomnika.v12i3.4565